Strategic Intelligence Analysis: Police Handling Efforts Against Security Threats in Electronic Commerce Transactions - Yulizar, Muhammad Agus; Puspitasari, Maria; Widiawan, Bondan (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
In the era of globalization and rapid development of information technology, electronic commerce transactions or E-commerce have become an integral part of business activities throughout the world. The growth of E-commerce in Indonesia began in 1999 and continues to grow rapidly along with increasing internet use. However, along with this development, cyber security threats have also emerged, such as online fraud, theft of personal data, and cyber-attacks. This research outlines the strategic intelligence steps taken by the Indonesian National Police (Polri) in dealing with security threats in electronic commerce transactions. Polri adopts a comprehensive approach involving planning, information gathering, data analysis, and policy making. They also collaborate with various related institutions and carry out educational campaigns to increase public understanding of the risks of cybercrime. This research then found that the National Police needed to strengthen cooperation with various parties, invest in advanced technology, monitor technological developments, and increase special investigation units. By taking these steps, the National Police can improve their ability to tackle cybercrime in electronic commerce transactions and create a more resilient digital security ecosystem.